1999
DOI: 10.1001/archneur.56.5.609
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of New-Onset Seizures in Patients With Human Immunodeficiency Virus Infection

Abstract: New-onset seizures are infrequent in patients with HIV. In most cases a definite or probable cause is identified, which is usually related to toxic and/or metabolic factors. Most seizures are generalized, and partial seizures suggest a focal cerebral lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
72
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 26 publications
16
72
6
Order By: Relevance
“…NOS in this study accounted for 2% of neurological manifestations. In clade B regions 3% of HIV patients in a prospective study and between 11% and 17% in retrospective studies were found to have suffered a newonset seizure at some time during their illness [20]. We previously described our experience with NOS in HIV and noted that in 75% of such patients the cause for the NOS was either meningitis or a SOL.…”
Section: Discussionmentioning
confidence: 99%
“…NOS in this study accounted for 2% of neurological manifestations. In clade B regions 3% of HIV patients in a prospective study and between 11% and 17% in retrospective studies were found to have suffered a newonset seizure at some time during their illness [20]. We previously described our experience with NOS in HIV and noted that in 75% of such patients the cause for the NOS was either meningitis or a SOL.…”
Section: Discussionmentioning
confidence: 99%
“…The development of neurological symptoms in HIV-infected patients is not uncommon and is related either primarily to HIV infection or secondarily to opportunistic infections (19). Since the frequency of new-onset seizures in HIV infection has been estimated to be 3% (22), there is a medical need to use anticonvulsants in the management of these patients. Similar to efavirenz, carbamazepine exhibits an autoinduction property and increases the metabolism of concomitantly administered drugs.…”
mentioning
confidence: 99%
“…Three other subjects presented with seizure disorder but did not have confirmatory radiological investigations done as they died soon after presentation. Seizures have been reported in 3-17% of AIDS-sick patients and the usual causes are drug toxicity and intracranial lesions (Wong, Suite & Labar, 1990;Pascual-Sedano, Iranzo, Marti-Fabregas, Domingo, Escartin, Fuster, Barrio & Sambeat, 1999). Most patients with brain mass lesions present with generalised seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with brain mass lesions present with generalised seizures. When partial seizures are present, they usually indicate an intracranial pathology, usually in the form of cerebral toxoplasmosis, cerebral lymphoma, cryptococcal meningitis and cerebral infarction (Wong et al, 1990;Pascual-Sedano et al, 1999). Direct HIV infection is also a cause of seizures without any brain lesion (Wong et al, 1990).…”
Section: Discussionmentioning
confidence: 99%